Reduction Method of Circulating Current for Parallel Connected Inverters Using Proportional Resonant Control - Choi, Hye Won; Lee, Kyo Beum (ICPE 2023-ECCE Asia - 11th International Conference on Power Electronics - ECCE Asia: Green World with Power Electronics, 2023)
This paper proposes a reduction method of circulating current for parallel connected inverters using proportional resonant (PR) control. Paralleled inverter has been increasingly applied in many power conversion systems such as renewable energy systems, motor drives, and energy storage systems. Modular inverters have several advantages of convenient maintenance and adjustable rating of power by the number of modules. However, a circulating current of paralleled inverter is generated due to the difference in the output parameters in each module. The circulating current distorts the quality of output current and deteriorates the performance of the parallel systems. To mitigate the problems, a reduction method is proposed using the PR controller of the paralleled connected inverter. The PR control method extracts the third harmonics of output current to reduce the circulating current of low-frequency component. The proposed method controls the low-frequency circulating current applying only controllers. The simulation results demonstrate the validity of the proposed control method.
Keywords: Circulating current; Control methods; Modular inverte; Modulars; Output current; Parallel connected inverte; Parallel-connected; Paralleled inverters; Proportional-resonant controls; Reduction method; Circulating Current; Modular Inverter; Parallel Connected Inverter; Proportional Resonant Control